EFEITO DO HISTÓRICO DE REFORÇAMENTO DA FORMAÇÃO EM DIFERENTES ÁREAS DO DISCURSO EXPLICATIVO DE ACADÊMICOS DE LICENCIATURA SOBRE O DESEMPENHO HIPOTÉTICO DE ESTUDANTES - PEDRO HENRIQUE ARAUJO ORLANDI (2023)
Skinner conceptualizes verbal behavior as operant behavior in which the consequence is mediated by a listener trained by the verbal community. One of the author's focuses would be on the scientific verbal behavior and consequently on the verbal behavior of explaining emitted by the scientist. Explanations would be, commonly, descriptions about causal relationships and would aim to promote the listener to be able to act concretely more effectively. The objective of this research was to analyze the effect of the history of training reinforcement in different areas on the explanatory discourse of undergraduate students on the performance contained in a hypothetical situation of two elementary school students. Participants from three courses were selected: Biology, Mathematics and History. The method used was the Reno Method, which is considered an effective alternative for analyzing discourses. The procedure consisted of presenting a written hypothetical situation to the participant, in which the academic performance of two students was described, one with high performance and the other not, and after reading this situation, questions were asked about the story to the participant and how he explains this. situation and how he would act if he himself were the teacher in question. The results indicate a consensus among the three participating groups, where they responded in unison in the macrocategories and categories of analysis, with a small difference in responses in group 2 - academics of History. The participants' response patterns were discussed, as well as discrepancies and analyzes in the participants' personal history and possible effects of the history of reinforcement of the degree studied on their responses. Finally, a functional description of the researcher's own explaining behavior was carried out.